2016
DOI: 10.1002/bit.25918
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PVDF‐TrFE scaffolds on stem cell derived cardiovascular cells

Abstract: Recently, electrospun polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE) scaffolds have been developed for tissue engineering applications. These materials have piezoelectric activity, wherein they can generate electric charge with minute mechanical deformations. Since the myocardium is an electroactive tissue, the unique feature of a piezoelectric scaffold is attractive for cardiovascular tissue engineering applications. In this study, we examined the cytocompatibility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 49 publications
3
79
0
1
Order By: Relevance
“…Stem cell derived cardiomyocytes and endothelial cells have been successfully cultured on PVDF-TrFE fibers before. [60] However, Adv. Mater.…”
Section: Differentiation and Maturation Of Human-induced Pluripotent mentioning
confidence: 99%
“…Stem cell derived cardiomyocytes and endothelial cells have been successfully cultured on PVDF-TrFE fibers before. [60] However, Adv. Mater.…”
Section: Differentiation and Maturation Of Human-induced Pluripotent mentioning
confidence: 99%
“…Degradation was apparent from week 4 and onwards, leading to the conclusion that the degradation ratio of the material is suitable for a large range of tissue engineering applications. Further, it was found that the degradation of the samples maintain the biocompatibility of the materials for the pristine polymer, but can lead to cytotoxic effects when the magnetic CFO nanoparticles are exposed, being therefore needed, for magnetoactive applications, to substitute them by biocompatible ferrites, such as an iron oxide (Fe 3 O 4 ).Polymers 2020, 12, 953 2 of 15In particular, smart polymers are gaining increasing attention as substrates and scaffolds for tissue engineering applications mainly as electroactive substrates-mostly piezoelectric ones-such as poly(l-lactic acid) (PLLA) [5,6], poly(hydroxybutyrate) (PHB) [7], poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) [8,9] and poly(vinylidene fluoride) (PVDF) [10,11], among others. The ability of those materials to actively enhance and stimulate cellular differentiation processes has been already proven [12,13], based on their mechano-transduction characteristics, generating voltage upon mechanical stimulation and vice-versa [14].…”
mentioning
confidence: 99%
“…In particular, smart polymers are gaining increasing attention as substrates and scaffolds for tissue engineering applications mainly as electroactive substrates-mostly piezoelectric ones-such as poly(l-lactic acid) (PLLA) [5,6], poly(hydroxybutyrate) (PHB) [7], poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) [8,9] and poly(vinylidene fluoride) (PVDF) [10,11], among others. The ability of those materials to actively enhance and stimulate cellular differentiation processes has been already proven [12,13], based on their mechano-transduction characteristics, generating voltage upon mechanical stimulation and vice-versa [14].…”
mentioning
confidence: 99%
“…Natural polymers are biodegradable, biocompatible and easily manipulated matrices composed of complex elements which make up the native tissue [103] The natural polymers used so far for cardiac repair include collagen, gelatin, alginate, silk, fibrin, chitosan and hyaluronic acid [67].…”
Section: Natural Polymers For Cardiac Scaffoldsmentioning
confidence: 99%